Ethnopolitical Discourse. A Theoretical Model Based on the Discursive Practices of Aymara Intellectuals (Palimpsesto, 2024)
The article formulates a theoretical model of ethnopolitical discourse based on the case of the Aymara intelligentsia of the extreme north of Chile. To do this, the text reflects on the conceptual link between intellectuality and discursive practice, focusing the abstraction process on this last meaning. The proposed typology is based on a series of regularities identified in the cultural and professional behavior of the subjects who were part of the case study. On this basis, the analytical scheme contemplates two fundamental dimensions: the first, a professional discursive practice; and the second, a cultural discursive practice. The first is linked to the degrees and types of instruction acquired in formal academic institutions. The second, on the other hand, is based on the cultural history of the subjects and how this serves - along with professional notions - as input for the formulation of a type of political discourse in Chile. In this way, ethnopolitical discourse is understood as a speech act and as a social formula. The model also includes components and indicators for research. On this basis, the text ends with a series of methodological suggestions on how to adapt archival and field procedures to objectify the typology in a specific analytical field.
Keywords: ethnopolitical discourse; theoretical model; discursive practices; Aymara; Chile